The Dominance of Gamelan in South Korea in a Discursive Perspective - Ji Tae, Chung; Faruk, Faruk; Rahadianto Sutopo, Oki (KnE Social Sciences, 2023)
This article provides a genealogical investigation through a postcolonial perspective about gamelan discourses in South Korea. Gamelan is known as a traditional orchestra representative of Indonesia, especially in academic circles. Whereas Indonesian culture is still not well known in South Korea, Indonesian traditional instruments are not limited to gamelan. There are also a great many other traditional instruments on each island and among different ethnic groups in the nation. How and why has gamelan come to be seen as such a representative Indonesian musical instrument within South Korea? Knowledge of gamelan or Indonesian music is a more recent issue in South Korea where there has been no long history of Indonesian musical discourse. The aim of this article is therefore to understand how gamelan was decontextualized from its origin through orientalism and colonial era research into the performing arts, and how this led to it becoming a representative Indonesian traditional music form in South Korea throughFoucault’s theory of discourse. To do this, historical data was investigated using genealogical methodology. Gamelan was one of the popular objects during the colonial era for Western musicians and musicologists. The popularity of gamelan has been parallel with the development of ethnomusicology, and it has flown into South Korea with increasing Korean students who study in the West and through interactions between musicologists in the ethnomusicology field. Keywords: Korean gamelan, Indonesian music, colonialism, postcolonial, ethnomusicology